Sustainability Reporting: Empirical Evidence from Listed Firms of Fuel and Power Sector of Bangladesh - Haque, Tanzina; Rahman, Md Musfiqur (Dhaka University Journal of Business Studies, 2021)
The aim of this study is to observe the extent of sustainability reporting practice and to investigate the influential factors in determining the sustainability reporting in the fuel and power industry of Bangladesh. This research study develops a self-structured sustainability reporting index (SRI) based on established guidelines and previous studies. Content analysis has been used to observe the practice of sustainability reporting and board composition, ownership structure and firm characteristics have been used as the proxies of determinants of sustainability reporting. The study found that the average mean of sustainability reporting measured by the index is only 20.14% which indicates a very poor quality of sustainability reporting. Among the three components of sustainability reporting, economics sustainability disclosure has the highest index value and environmental sustainability disclosure has the lowest index value. But the positive sign is that the disclosure level of sustainability reporting is gradually increasing over the years. The multiple regression result shows that sustainability reporting practice is more prevalent inbigger firms and older firms. This study also shows that there is no significant association of sustainability reporting with board composition and ownership structures which implies that corporate governance instruments are not playing their effective role in ensuring sustainability reporting. The results recommend that the regulatory authority should develop mandatory guidelines for sustainability reporting or enforce existing global guidelines like GRI to improve the practice of sustainability reporting. The study also suggests that efficient corporate governance mechanism may play a vital role in increasing the extent of sustainability reporting in Bangladesh. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 175-212